Circuitos turísticos no Brasil: Governança e políticas públicas - Fuini Labigalini, Lucas [UNESP] (My University, 2014)
The Tourist Circuits (TCs) are a recent theme in public policy for tourism in Brazil. The concept of TCs includes a particular geographical area, characterized by the predominance of cultural, historical and natural elements, creating an identity between municipalities in a council, by private and public initiative, to complement the attractions and tourist facilities in order to enhance the flow and permanence of visitors, and generate employment and income. It is a concept and tool of governance for land planning and tourism management in the face of a growing movement of national tourism policy decentralization at the state and municipality level. The aim of this paper is to investigate the TCs as a new type of land governance of tourism in Brazil, presenting their main characteristics, empirical examples and their strengths and weaknesses as a tool for local and regional territorial development.
Tourist circuits in Brazil: Governance and public policy
Keywords: Land governance; Public policy; Tourism in Brazil; Tourist circuits